OPTIMALISASI WEBSITE SEBAGAI STRATEGI DIGITAL MARKETING UNTUK MENINGKATKAN MINAT KUNJUNG PASIEN POLI GIGI RUMAH SAKIT UNIVERSITAS MUHAMMADIYAH MALANG - Rosa Wisatya, Meirina (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2024)
Website Optimization As a Digital Marketing Strategy to Increase Interest in Visiting Patients at the Dental Poly Hospital Muhammadiyah University of Malang. Digital marketing has experienced significant progress in recent years. The strategy implemented by the hospital to increase visits is by implementing digital marketing. The strategy for implementing Digital Marketing is expected to attract patient visits at UMM Hospital, especially the dental clinic, to increase patient visits. As a result of identifying the root of the problem, it is necessary to optimize the website as a digital marketing strategy. The aim of this research is to determine the importance of website optimization as a digital marketing strategy. This research used a pre-experiential one group design with pre and post intervention without control. The research sample was the staff of the digital Public Relations and Marketing division at UMM Hospital. Data analysis used descriptive analysis and the research results showed that there was an increase in knowledge after sharing the material. The conclusion is that the increase in knowledge regarding website optimization among digital PR and Marketing staff is quite significant, but this needs to be continued by receiving certified training.